Public experiences of court: how victims, defendants and witnesses perceive and make sense of the criminal justice process, 2011-2012 - Jacobson, J. (UK Data Service, 2014)
This project examined the public's experiences of the Crown Court. More specifically, it focused on the extent to which victims, defendants and witnesses understand court proceedings and perceive them to be fair, and believe that they are treated politely and respectfully by the court. The research identified the factors which determine levels of understanding and perceptions of fair and respectful treatment. There were three main aims of the study. First, it explored the extent to which personal experiences of court had a bearing on the trust that individuals have in the criminal justice system as a whole. The second aim was to identify the main barriers to individuals' - and particularly defendants' - understanding of, and engagement with, court proceedings. The third aim was to draw out the commonalities in victims', defendants' and witnesses' experiences of court. The study entailed fieldwork at two Crown Courts; one in an urban city and the other in a small town. The main component of the fieldwork was in-depth, semi-structured interviews with victims, defendants and witnesses. The research team also undertook observations of court proceedings, including trials and sentencing hearings. In addition, the researchers conducted in-depth, semi-structured interviews with court professionals and staff at the beginning of the fieldwork which acted as a useful scoping exercise for the remainder of the research. Further information and links to publications may be found on the The public's experiences of court: how victims, defendants and witnesses perceive and make sense of the criminal justice process award webpage.